Total communication, bimodal-bilingual programs and translanguaging in deaf education in South Africa: the case for teaching English additional language poetry - Bohringer, Colleen Ruth (My University, 2022)
A thematic analysis of three case studies at schools for Deaf children in South Africa, focusing on the core aspects of modes of communication, language and identity, and teaching English additional language poetry in the context of Deaf education. The study explored each schools’ approach to bilingual-bicultural teaching through the lens of teaching and learning English additional language poetry. Using a qualitative ethnographic multiple case study method, poetry lessons were observed and documented; teachers, learners and supporting staff were interviewed; and detailed fieldnotes were recorded. Poetry straddles Bakhtinian chronotope of the poet’s reality in time and space, and the subordinated literary chronotope of that reality suspended in the time and space of the text. Learners and teachers experience the literary chronotope differently as it is filtered through their individual cognitive schema, experiences, social interactions, textual cues, and education. This process in a sense expands the subordinated literary chronotope by creating a text world relevant to the time and space of the learners and teacher. This study acknowledges the critical complexity inherent in an English additional language poetry classroom, further compounded by the language and modality used in teaching poetry in the context of Deaf education. In an English additional language poetry classroom where the role of knowledge and the knower have the potential to either inhibit or encourage critical dialogue that is required to engage with the ideology inherent in poetry; language and identity as well as modes of communication play a significant part. The results identify degrees of ‘unequal encounter’ in an English additional language poetry classroom as a product of inadequate proficiency in linguistic resources that are needed as semiotic resources for dialogue and critical analysis.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education in Deaf Education to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022